JOHN SKILLPA’S DISSOCIATIVE DISORDERS IN PEACOCK - IRFANTARA, DHIMAS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Mental Disorders, Dissociative Disorders, Movie Study, Peacock Dissociative disorder in general refers to a disorder that causes someone find difficulties in mingling with others, since he or she has multiple personalities. Someone who lives with the phenomenon of dissociative disorder found in Peacock the movie.The result from the thesis shows that the main character of the movie, John Skillpa suffers mental disorder. The type of mental disorder suffered by John Skillpa is dissociative disorder. Dissociative disorder can be categorized into four disorders namely dissociative amnesia, dissociative fugue, depersonalization disorder, and dissociative identity disorder. By having these four disorders, John Skillpa finally has multiple personality.The writer suggests that the next researchers to apply other perspectives in analyzing the movie, such as anxiety approach to analyze anxiety of main character in the film.